2005
DOI: 10.1091/mbc.e05-04-0294
|View full text |Cite
|
Sign up to set email alerts
|

RasMutation Impairs Epithelial Barrier Function to a Wide Range of Nonelectrolytes

Abstract: Although ras mutations have been shown to affect epithelial architecture and polarity, their role in altering tight junctions remains unclear. Transfection of a valine-12 mutated ras construct into LLC-PK 1 renal epithelia produces leakiness of tight junctions to certain types of solutes. Transepithelial permeability of D-mannitol increases sixfold but transepithelial electrical resistance increases >40%. This indicates decreased paracellular permeability to NaCl but increased permeability to nonelectrolytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 50 publications
(60 reference statements)
1
28
2
Order By: Relevance
“…It can thus be suggested that the elevated pathogenic character of RASV12 transfected FTC-133 cells involves the increase of CLAUDIN-1 protein expression. This increase in CLAUDIN-1 expression after RASV12 transfection was also observed in normal renal epithelial cells, whereby in these normal cells CLAUDIN-1 was localized in the cell membrane (Mullin et al 2005). As a side note, we tried CLAUDIN-1 downregulation by CLAUDIN-1 siRNA transfection of RASV12 transfected FTC-133 cells, which resulted in cell death within a few hours, potentially due to the augmented stress of cells, and irrespective if cells were transfected either with control siRNA or CLAUDIN-1 siRNA transfection mixture (unpublished observation).…”
Section: Discussionsupporting
confidence: 63%
“…It can thus be suggested that the elevated pathogenic character of RASV12 transfected FTC-133 cells involves the increase of CLAUDIN-1 protein expression. This increase in CLAUDIN-1 expression after RASV12 transfection was also observed in normal renal epithelial cells, whereby in these normal cells CLAUDIN-1 was localized in the cell membrane (Mullin et al 2005). As a side note, we tried CLAUDIN-1 downregulation by CLAUDIN-1 siRNA transfection of RASV12 transfected FTC-133 cells, which resulted in cell death within a few hours, potentially due to the augmented stress of cells, and irrespective if cells were transfected either with control siRNA or CLAUDIN-1 siRNA transfection mixture (unpublished observation).…”
Section: Discussionsupporting
confidence: 63%
“…The penetration of factors such as IGF-I into these areas may signify a local loss of epithelial barrier function, and it has been suggested that a local breach in the epithelial barrier may be an early event in tumor formation (22). We have shown that oncogenic conversion of epithelial cells produces profound changes in epithelial barrier function (23), and it has been reported that seminal fluid can alter epithelial barrier function in vitro (24,25). This supports the idea that factors from the seminal fluid enter the basal compartment in the prostate where these factors can influence basal cell proliferation.…”
Section: Discussionmentioning
confidence: 73%
“…ï€Ș ERK has a variable effect on the integrity of epithelial tight junctions; it can disrupt tight junction integrity in some cases 121,122,125,126 whereas, it can also protect tight junction integrity in other cases. 94,123 The mechanistic basis for this paradoxical ERK activity in tight junction regulation remains unclear.…”
Section: Chapter 5: Discussionmentioning
confidence: 99%
“…124 Another study showed that a mutation in Ras (a signaling molecule upstream of ERK) is associated with increase in extra cellular signal-regulated kinase-2 phosphorylation and produces leakiness of tight junctions to certain types of solutes. 125 Similarly, Raf-1-another signaling molecule upstream of ERK has been implicated in causing disruption of epithelial TJs via downregulation of occludin. 126 Another study demonstrated that downregulation of the MAPK signaling pathway causes the restoration of epithelial cell morphology and the assembly of tight junctions in Ras-transformed epithelial cells and that tyrosine phosphorylation of occludin and ZO-1 may play a role in some aspects of tight junction formation.…”
Section: Erk In Regulation Of Tight Junctionsmentioning
confidence: 99%
See 1 more Smart Citation